Conjuring Trauma with (Self)Derision: The African and African-American Epistolary Fiction - Ousmane Ngom (European Scientific Journal, ESJ, 2018)
All the female narrators of the three stories examined here – So Long a Letter, The Color Purple, and Letters from France – suffer serious traumas attributable to their male counterparts. Thus as a healing process, letter-writing is an exercise in trust that traverses the distances between the addresser and the addressee. Blurring the lines in such a way results in an intimate narration of trauma that reads as a stream of consciousness, devoid of fear of judgment or retribution. This paper studies the literary device of derision coupled with a psycho-feminist analysis to retrace the thorny, cathartic journey of trauma victims from self-hate to self-acceptance and self-agency.